Preliminary results for a three-dimensional printer novel approach in nasal molding for infants with unilateral cleft lip and palate - Mayra Alvarez; Daniela Scarlett Escobar; Tatiana Castillo; Evelyn Gonzalez Hernandez; Akhilanand Chaurasia; Monica Dominguez; Adriana Reyes; Alejandro Munoz Paz; Maria Del Rosario Montoya Castillo; Jose Manuel Hernandez; Marcia Perez Dosal; Martha Mejia (Wolters Kluwer Medknow Publications, 2024)
Background: Presurgical orthopedics (PSO) can be used to treat patients with cleft lip and palate. PSO is a powerful tool for changing nasolabial and palate structures during the 1st months of life, helping improve the restoration of form and essential functions. Materials and Methods: This preliminary retrospective pilot study evaluated treatment efficacy with a nasal PSO protocol using the Rhinoplasty Appliance System (RAS) in seven centers in Mexico that specialize in managing children born with cleft lip and palate. Twenty-five unilateral cleft lip and palate patients (UCLP) (9 females and 16 males) were treated by an orthodontist trained in the RAS system. The severity of the cleft, treatment time, the number of devices used during treatment, and clinical complications were documented using a survey. The results were measured using standardized submental view two-dimensional photographs. Two independent investigators evaluated one angular variable and two lineal variables before and after treatment. The columella deviation angle was measured.On the affected side, between the line in the middle of the columella from anthropometric points Sn-Prn and reference line between Sn-Sbal. The lineal variables that compare the healthy and cleft sides were measured as ratios. The lineal variables were nostril width (this measurement is taken from all are anthropometric points to the columella on the horizontal plane) and nostril height (from the nasal base plane to the upper part of the nostril). All relevant data are within the paper and its supplementary information files. Results: The resulting data were analyzed using a paired t-test (P < 0.05). The results of nasal symmetry showed a statistically significant decrease in the nostrils' midline deviation and horizontal symmetry and a statistically significant increase in unilateral patients' vertical symmetry and tip-base angle. Of the reported complications, 36% of orthodontists did not express any concerns. Meanwhile, 32% experienced skin irritation on the cheeks, 16% faced challenges with treatment attachment, 12% encountered difficulties in applying the correct tractions on the rubber bands, and 4% required a larger device from the system. Conclusions: In these preliminary results, the Rhinoplasty Appliance System (RAS) streamlines procedures, enhances reproducibility, and offers a practical solution for nasal protocols in managing cleft lip and palate in infants. RAS improves nasal symmetry, displaying promising outcomes in holistic care for infants with UCLP conditions. This research highlights the potential of three-dimensional printing and innovative digital approaches to revolutionize presurgical interventions for pediatric patients, particularly in infant nasal PSO.